Glucocorticoids, inflammation and bone loss - Roux, Christian (Henry Stewart Talks, 2015)
Direct & indirect effects of glucocorticoids on bone, Management of Glucocorticoid-Induced Osteoporosis (GIOP), Inflammation and bone loss in back pain & rheumatoid arthritis (RA), Cytokines, T lymphocytes & autoimmunity in bone loss, Sclerostin inhibition, PTH and inflammation effects on bone formation, Anti-TNF effects on bone remodeling, BMD and fractures